Epidemiology of Trypanosomiasis in Wildlife—Implications for Humans at the Wildlife Interface in Africa - Kasozi, Keneth Iceland; Zirintunda, Gerald; Ssempijja, Fred; Buyinza, Bridget; Alzahrani, Khalid J.; Matama, Kevin; Nakimbugwe, Helen N.; Alkazmi, Luay; Onanyang, David; Bogere, Paul; Ochieng, Juma John; Islam, Saher; et al. (Frontiers in Veterinary Science, 2021)
While human and animal trypanosomiasis continue to present as major human and animal public health constraint globally, detailed analyses of trypanosome wildlife reservoir hosts remain sparce. African Animal Trypanosomiasis affects livestock and wildlife with significant risk of spillover and cross transmission of species and strains between populations, due to the increasingly close proximity between human settlements and grazing lands to wildlife reserves and game parks. Increased human activity together with pressure on land resources is exacerbating wildlife-livestock-human infections. Communities living and maintaining livestock on the fringes of wildlike rich ecosystems require to control vector transmission and treat livestock to prevent trypanosomiasis. Major Trypanosoma spp include: T.b.rhodesiense and T. b. gambiense and T. cruzi, pathogenic for humans and T. vivax, T. congolense, T. evansi, T. b. brucei, T. dionisii, T. thomasbancrofti, T. elephantis, T. vegrandis, T. copemani, T. irwini, T. copemani, T. gilletti, T. theileri, T. godfreyi, T. simiae and Trypanosoma (Megatrypanum) pestanai. Wildlife hosts for the trypansomatidae include families of Bovinae, Suidae, Pantherinae, Equidae, Alcephinae, Cercopithecinae, Crocodilinae, Pteropodidae, Peramelidae, Sigmodontidae, Meliphagidae. Wildlife species are generally considered tolerant to trypanosome infection following centuraries of coexistence of vectors and wildlife hosts. Tolerance is influenced by age, sex, species and physiological condition, parasite challenge, and vector reproduction. Cyclic transmission through tsetse flies occurs for T. congolense, T simiae, T vivax, T brucei and T.b. rhodesiense, T.b. gambiense and within Rejuvid bugs for T. cruzi. T. evansi is mechanically transmitted and T. vixax is also commonly transmitted by biting flies including tsetse. Wildlife animal species serve as long-term reservoirs of infection but the delicate acquired balance between trypanotollerance and trypanosome challenge, can be disrupted by an increase in challenge and/ or introduction of new more virulent species into the ecosystem. There is a need to protect wildlife and animal and human propulations from the infectous consequences of encroachment, to preserve and protect these populations. In this review we explore the ecology and epidemiology of Trypanosoma spp. in wildlife.